FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN PERUSAHAAN MANUFAKTUR DALAM MELAKUKAN INOVASI PRODUK DI INDONESIA - Widya Septyati; Rachmat Pambudi; Lukman M Baga (Jurnal Sosial Humaniora, 2022)
Innovation is an important factor for the survival and growth of firms. Based on the value of Competitive Industrial Performance (CPI), the innovation performance of Indonesian manufacturing companies shows a fluctuating trend, lags behind other neighboring countries and have a low level of innovation awareness. This study aims to analyze the factors that influence Indonesian manufacturing firms on product innovation. The article uses logit regression method and secondary data focusing on 1,069 Indonesian manufacturing companies in 2015. The results showed that product innovation was positively and significantly influenced by the manager's work experience, total sales, exports and R&D. From these results, it can be concluded that to improve the innovation performance of Indonesian manufacturing firms, policies should be aimed at the factors which influence product innovation significantly.